MODEL CONCEPT ATTAIMENT BERBASIS ORGANISER TEKNOLOGI TRADISIONAL UNTUK PENGUATAN LITERASI SAINS GLOBAL DAN KARAKTER KREATIF - Soka Hadiati; Adi Pramuda; Matsun (Postgraduate, University of Mataram, 2024)
This study aims to obtain a concept attaiment model based on traditional technology organizers that is feasible, practical, and effective to strengthen global science literacy and creative character. This research uses the Borg and Gall development research model with stages, including: information collection research, planning, initial development, initial testing (initial field testing), main product revision, main testing (main field testing), operational product revision, operational field testing, final product revision, and dissemination. Exploration of traditional technology is carried out to obtain experimental media that will be summarized into organizers for learning media. Hypothetical model validation (FGD-focus group discussion) involves lecturers and education practitioners in West Kalimantan to obtain eligibility. Limited initial field testing with purposive sampling techniques at IKIP PGRI Pontianak with a pre-experimental one group pretest posttest design. Global science literacy is measured using questionnaires. Creative character is measured using scientific creativity tests referencing divergent thinking. The results of the study obtained a concept attaiment model based on traditional technology organizers to strengthen global science literacy and valid creative characters with excellent criteria. The t-test results show that the concept attaiment model based on traditional technology organizers is effective for improving global science literacy and creative character. Students and educators respond well to the application of concept attaiment models based on traditional technology organizers.